2001
DOI: 10.1128/jcm.39.9.3156-3163.2001
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunosorbent Assay for Detecting Herpesvirus Exposure in Mediterranean Tortoises (Spur-Thighed Tortoise [Testudo graeca] and Hermann's Tortoise [Testudo hermanni])

Abstract: Herpesviruses are well-known infectious agents with remarkably wide host ranges. Starting in 1975 (33), several reports have documented the presence of herpesvirus-like particles in land tortoises and freshwater and marine turtles (5, 7-9, 11, 15, 17, 19-23, 27-29, 30, 38). Recent investigations have revealed an association between the presence of herpesvirus and an upper respiratory tract disease in Mediterranean tortoises [spur-thighed tortoise (Testudo graeca) and Hermann's tortoise (T. hermanni)] (5,8,9,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
96
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 19 publications
(16 reference statements)
3
96
0
Order By: Relevance
“…It has been suggested that distinct herpesviruses are adapted to different species of tortoises, and Testudo spp. seem to be the most vulnerable (Origgi and Jacobson, 2000). Bacteria have also been suggested to play a role in respiratory disease in tortoises (Biberstein and Fowler, 1980;Snipes and Biberstein, 1982;Lawrence and Needham, 1985), although these have also been recovered from apparently healthy tortoises (Martinez-Silvestre and Mateu, 1997).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that distinct herpesviruses are adapted to different species of tortoises, and Testudo spp. seem to be the most vulnerable (Origgi and Jacobson, 2000). Bacteria have also been suggested to play a role in respiratory disease in tortoises (Biberstein and Fowler, 1980;Snipes and Biberstein, 1982;Lawrence and Needham, 1985), although these have also been recovered from apparently healthy tortoises (Martinez-Silvestre and Mateu, 1997).…”
mentioning
confidence: 99%
“…1). Seroconversion of tortoises to both types of ChHV (I and II) has been demonstrated 4 wk following infection (Origgi et al, 2001) but coinfection had not been previously described. Interspecific coinfection (M. agassiziiChHV) was described by Soares et al (2004) but the type of ChHV was not identified.…”
mentioning
confidence: 99%
See 3 more Smart Citations